### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

minus(x, 0) → x
minus(s(x), s(y)) → minus(x, y)
quot(0, s(y)) → 0
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0, y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
minus(s(x), s(y)) →+ minus(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
minus, quot, plus, app, sum, gt

They will be analysed ascendingly in the following order:
minus < quot
plus < minus
plus < sum
gt < plus
app < sum

### (8) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
app, minus, quot, plus, sum, gt

They will be analysed ascendingly in the following order:
minus < quot
plus < minus
plus < sum
gt < plus
app < sum

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Induction Base:
app(gen_nil:cons4_0(0), gen_nil:cons4_0(b)) →RΩ(1)
gen_nil:cons4_0(b)

Induction Step:
app(gen_nil:cons4_0(+(n6_0, 1)), gen_nil:cons4_0(b)) →RΩ(1)
cons(0', app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b))) →IH
cons(0', gen_nil:cons4_0(+(b, c7_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
gt, minus, quot, plus, sum

They will be analysed ascendingly in the following order:
minus < quot
plus < minus
plus < sum
gt < plus

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)

Induction Base:
gt(gen_0':s:zero:true:false3_0(+(1, 0)), gen_0':s:zero:true:false3_0(+(1, 0)))

Induction Step:
gt(gen_0':s:zero:true:false3_0(+(1, +(n1024_0, 1))), gen_0':s:zero:true:false3_0(+(1, +(n1024_0, 1)))) →RΩ(1)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) →IH
*5_0

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
plus, minus, quot, sum

They will be analysed ascendingly in the following order:
minus < quot
plus < minus
plus < sum

### (15) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)

Induction Base:
plus(gen_0':s:zero:true:false3_0(0), gen_0':s:zero:true:false3_0(b)) →RΩ(1)
gen_0':s:zero:true:false3_0(b)

Induction Step:
plus(gen_0':s:zero:true:false3_0(+(n2215_0, 1)), gen_0':s:zero:true:false3_0(b)) →RΩ(1)
s(plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b))) →IH
s(gen_0':s:zero:true:false3_0(+(b, c2216_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (17) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
minus, quot, sum

They will be analysed ascendingly in the following order:
minus < quot

### (18) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)

Induction Base:
minus(gen_0':s:zero:true:false3_0(+(1, 0)), gen_0':s:zero:true:false3_0(+(1, 0)))

Induction Step:
minus(gen_0':s:zero:true:false3_0(+(1, +(n4005_0, 1))), gen_0':s:zero:true:false3_0(+(1, +(n4005_0, 1)))) →RΩ(1)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) →IH
*5_0

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (20) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
quot, sum

### (21) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol quot.

### (22) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

The following defined symbols remain to be analysed:
sum

### (23) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
sum(gen_nil:cons4_0(+(1, n6845_0))) → gen_nil:cons4_0(1), rt ∈ Ω(1 + n68450)

Induction Base:
sum(gen_nil:cons4_0(+(1, 0))) →RΩ(1)
cons(0', nil)

Induction Step:
sum(gen_nil:cons4_0(+(1, +(n6845_0, 1)))) →RΩ(1)
sum(cons(plus(0', 0'), gen_nil:cons4_0(n6845_0))) →LΩ(1)
sum(cons(gen_0':s:zero:true:false3_0(+(0, 0)), gen_nil:cons4_0(n6845_0))) →IH
gen_nil:cons4_0(1)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (25) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)
sum(gen_nil:cons4_0(+(1, n6845_0))) → gen_nil:cons4_0(1), rt ∈ Ω(1 + n68450)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (26) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (28) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)
sum(gen_nil:cons4_0(+(1, n6845_0))) → gen_nil:cons4_0(1), rt ∈ Ω(1 + n68450)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (29) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (31) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)
minus(gen_0':s:zero:true:false3_0(+(1, n4005_0)), gen_0':s:zero:true:false3_0(+(1, n4005_0))) → *5_0, rt ∈ Ω(n40050)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (32) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (34) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)
plus(gen_0':s:zero:true:false3_0(n2215_0), gen_0':s:zero:true:false3_0(b)) → gen_0':s:zero:true:false3_0(+(n2215_0, b)), rt ∈ Ω(1 + n22150)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (35) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (37) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
gt(gen_0':s:zero:true:false3_0(+(1, n1024_0)), gen_0':s:zero:true:false3_0(+(1, n1024_0))) → *5_0, rt ∈ Ω(n10240)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (38) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (40) Obligation:

TRS:
Rules:
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
quot(0', s(y)) → 0'
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
minus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
0' :: 0':s:zero:true:false
s :: 0':s:zero:true:false → 0':s:zero:true:false
quot :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
plus :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s:zero:true:false → nil:cons → nil:cons
sum :: nil:cons → nil:cons
if :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
gt :: 0':s:zero:true:false → 0':s:zero:true:false → 0':s:zero:true:false
not :: 0':s:zero:true:false → 0':s:zero:true:false
id :: 0':s:zero:true:false → 0':s:zero:true:false
zero :: 0':s:zero:true:false
true :: 0':s:zero:true:false
false :: 0':s:zero:true:false
hole_0':s:zero:true:false1_0 :: 0':s:zero:true:false
hole_nil:cons2_0 :: nil:cons
gen_0':s:zero:true:false3_0 :: Nat → 0':s:zero:true:false
gen_nil:cons4_0 :: Nat → nil:cons

Lemmas:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s:zero:true:false3_0(0) ⇔ 0'
gen_0':s:zero:true:false3_0(+(x, 1)) ⇔ s(gen_0':s:zero:true:false3_0(x))
gen_nil:cons4_0(0) ⇔ nil
gen_nil:cons4_0(+(x, 1)) ⇔ cons(0', gen_nil:cons4_0(x))

No more defined symbols left to analyse.

### (41) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
app(gen_nil:cons4_0(n6_0), gen_nil:cons4_0(b)) → gen_nil:cons4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)